Development of an Anopheles arabiensis sex separation strain and optimisation of mosquito handling, packaging and transport conditions for the South African Mosquito Sterile Insect Technique programme - Mashatola, Thabo (University of the Witwatersrand, Johannesburg, 2023)
South Africa is taking significant strides towards eliminating malaria transmission within its borders. However, existing vector control strategies that focus on indoor mosquito management face challenges with Anopheles arabiensis, the primary malaria vector. To bolster these efforts, the sterile insect technique (SIT) is being considered as an additional vector control strategy. SIT involves mass-rearing and sterilising specific pest insects, which are then released to mate with wild insects, effectively reducing the pest population. The South African SIT project faces a crucial challenge of efficiently separating female mosquitoes from the production line. This is because female mosquitoes are capable of transmitting the malaria parasite, making their elimination vital. Current methods like manual separation and resistance-based sorting have operational limitations and require further optimisation for field trials. To address this challenge, this thesis conducted optimisation and acclimatisation experiments on adult Anopheles arabiensis females, aiming to transition them to an artificial membrane feeding technique. Comparative assessments demonstrated that artificial blood-feeding methods utilising a Hemotek® membrane feeding system and hog casing could effectively replace conventional methods without significant detriment to reproductive fitness. Subsequently, the study explored the use of ivermectin, a toxicant, to spike blood during artificial feeding to target and eliminate females. An optimal concentration of ivermectin (7.5 ppm) was identified, showing potential for segregating females from males during laboratory rearing. However, complete female elimination within the desired timeframe was not achieved, indicating that this method serves as a secondary phase for female elimination. The study also investigated the use of genetic sexing strains (GSSs) to selectively eliminate females. Although efforts to induce temperature-sensitive lethal mutations temperature sensitive lethality mutations and random morphological variations were unsuccessful, further cross mating studies and insights from previous studies on thermosensitive strains from Cameroon informed future research aimed at developing GSSs tailored to the South African genetic background Another challenge addressed was the optimal temperature and compaction conditions for chilling and immobilising sterile males during handling and transport. This is crucial for maintaining the quality of sterile males. Optimal knockdown temperature ranges (4°C – 8°C for 20 minutes) and packaging conditions (1000 sterile, marked adult males per 27000 cm³ Bugdorm-1® cage) were identified for laboratory handling and transport, facilitating recent small-scale pilot trials with successful packaging and transportation of sterile males to field sites. These advancements signify significant strides in South Africa's malaria elimination endeavours, while also playing a pivotal role in shaping the development of efficient operational protocols for SIT. Furthermore, as the country remains steadfast in its commitment to eliminating malaria, these innovative approaches offer a promising trajectory forward and establish a robust framework for orchestrating the SIT operational phase.
A dissertation submitted in fulfillment of the requirements for the degree of Doctor of Philosophy (PhD) in Medicine School of Pathology, Faculty of Health Science, to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, University of the Witwatersrand Johannesburg, 2023
Keywords: Anopheles arabiensis; Mosquito handling; Packaging and transport conditions; South African Mosquito Sterile Insect Technique programme; UCTD; SDG-3: Good health and well-being